Investigation of Principals' Technology Leadership Profiles in the context of Schools' Learning Organization Culture and ICT Infrastructure: F@tih Project Schools vs. the Others - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2016)
Although there is a growing body of literature about the integration of information and communication technologies (ICT) into K-12 schools and the ways how individually school principals can lead and support these initiatives, little is known about to what extent principals' technology leadership (TL) practices are predictable by school's organization culture and present ICT infrastructure. Hence, in this exploratory study, we set out to classify Turkish principals by their TL practices into discrete TT, profiles, taking individual, cultural and infrastructural factors into consideration. The five standards of International Society for Technology in Education (ISTE-2009) were taken as the measures of TL practices. Some main components of the learning organization (LO) culture such as team learning, shared vision and systems thinking disciplines were regarded as the measures of school culture. Principal's age and gender demographics, computer and internet usage frequency, school's F@tih project status and teachers' perception of LO culture were used as predictor variables. The current study surveyed 1105 teachers and 58 principals from 69 K-12 public schools located in Istanbul city. Latent class analysis (LCA) was used to assign principals to distinct TL profiles. Afterwards, logistic regression analysis was undertaken to determine significant predictors of the outcome TL profiles. The results revealed that Turkish principals assume two different profile of TL practices, leveled as high and low profiles. Almost 55% of the principals were delineated in the high-profile structure due to their strong interest to perform ISTE standards, whereas 45% of the principals were classified in the low-profile structure because of their relatively poor interest in the standards. The most striking result to emerge from this research is that Turkish principals are most likely to perform high-profile TL, practices when having: a) run a F@tih project school; b) used internet technology more frequently, c) managed a school in which teachers perceive a higher level of team learning LO culture, changing odds ratios from 4 up to 26 times higher.
Keywords: Technology leadership; ISTE standards; Fatih project; Learning organization; School culture; Latent class analysis; INTEGRATION